A rare case of microfilaria in thyroid aspirate - Mondal, Rajib Kumar; Ray, Rudranarayan; Kawsar, Hena; Ali, Md Sadakkas (Bangladesh Journal of Medical Science, 2014)
Filariasis is a major health problem in the Indian Subcontinent. Due to its nocturnal periodicity it may be difficult even to demonstrate in the blood. In heavy parasitic load they may appear in the blood, urine with chyle and at times in scrotal aspirates. It is very rare and unusual to find microfilaria in thyroid aspirate. This case report of presence of microfilaria in thyroid aspirate suggest that careful screening is important for thyroid lesions as patients may present with thyroid enlargement other than usual thyroid lesions. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14217 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 99-100